1996
DOI: 10.1093/nar/24.14.3071
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Fidelity of Thermus Thermophilus DNA Ligase

Abstract: The DNA ligase from Thermus thermophilus (Tth DNA ligase) seals single-strand breaks (nicks) in DNA duplex substrates. The specificity and thermostability of this enzyme are exploited in the ligase chain reaction (LCR) and ligase detection reaction (LDR) to distinguish single base mutations associated with genetic diseases. Herein, we describe a quantitative assay using fluorescently labeled substrates to study the fidelity of Tth DNA ligase. The enzyme exhibits significantly greater discrimination against all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 52 publications
3
65
1
Order By: Relevance
“…[2][3][4][5][6][7] In the PCR/LDR assays, following PCR amplification of the appropriate gene fragments, which contain sections of the gene(s) that possess the point mutations, the amplicon is mixed with two LDR primers (common primer and discriminating primer) that flank the mutation of interest at an appropriate temperature. The discriminating primer contains a base at its 3′-end that coincides with the single base mutation site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7] In the PCR/LDR assays, following PCR amplification of the appropriate gene fragments, which contain sections of the gene(s) that possess the point mutations, the amplicon is mixed with two LDR primers (common primer and discriminating primer) that flank the mutation of interest at an appropriate temperature. The discriminating primer contains a base at its 3′-end that coincides with the single base mutation site.…”
Section: Introductionmentioning
confidence: 99%
“…If there is a mismatch, no ligation of the two primers will occur. On the other hand, a perfect match results in a successful ligation of the two primers and produces a product that can be analyzed in a variety of fashions such as gel electrophoresis 3,4,7 and hybridization. 2,5,6 However, those post-LDR processes to separate the LDR products from the residual primers prior to detection are cumbersome, are the most time-consuming step in the entire assay procedure, making it difficult to quickly determine if mutated DNAs are present in samples.…”
Section: Introductionmentioning
confidence: 99%
“…Burgner et al observed that mismatch stability was increased in the presence of 3-nitropyrrole (1), and suggested that allelespecific, sequence-specific oligonucleotide hybridization could be used as a method for high-throughput genotyping of SNPs [62]. Luo et al similarly employed 3-nitropyrrole to enhance mismatch discrimination by a thermophilic DNA ligase, and used this as a method to isolate and characterize mutant ligases [63]. Bimolecular beacons have also been used to study SNPs; introducing 5-nitroindole (2) as an artificial mismatch achieves a clear differentiation between a perfect match and a single-base mismatch.…”
Section: Applications Of Universal Base Analoguesmentioning
confidence: 99%
“…[38][39][40][41][42] There are, however, a number of potential applications in which it would be useful to be able to join DNA strands without the need for ligase enzymes, as long as high fidelity in ligation could be maintained. After the first report of ligation that does not depend on the enzyme, 43 several research groups have been engaged in gene detection using ligation based on a variety of chemical reactions.…”
Section: Chemical Ligationmentioning
confidence: 99%